Pengelolaan Warisan Budaya Bangka: Inkonsistensi Kebijakan, Regulasi dan Partisipasi Publik - Iskandar Zulkarnain (Society, 2015)
This study aimed to describe government policy in managing the cultural heritage as a basis for legal regulation spawned cultural heritage management can strengthen the identity. This study uses qualitative policy analysis. Policy analysis seeks to influence the policy-making process "through research and arguments that not only supports the analysis of "problem", but also an analysis of what options or alternative policies to be taken". The results showed that the cultural heritage management policy which consists of the management of cultural heritage and the management of cultural heritage objects in Bangka generally been contained in the strategic documents the district level. Strategic documents such as RPJMD, RKPD, Renstra, and RTRW district policy contains clear enough about the efforts to optimize the development of culture and tourism program. But, in terms of implementation of cultural heritage management is still hampered by the absence of regulationsgoverning technical matters in the management of cultural heritage. The issue of the lack of regulation has an impact on the emergence of various internal constraints in the field of culture and tourism as well as cross-sectoral as seen from the unavailability of an expert team of cultural heritage, human resources competent in the field of culture, inconsistent implementation of culture, cultural heritage and knowledge of cultural heritage objects are less effective in the community. This affects the level of public participation in the management of cultural heritage in the future.